VD_FINDINFO AI 74/11 - 171/2012 vom 21. Mai 2012 - VD Tribunal cantonal (2012)
ÉVALUATION DE L'INCAPACITÉ DE TRAVAIL, EXPERTISE PSYCHIATRIQUE, SURVEILLANCEEN GÉNÉRAL | 28 LAI, 29 al. 1 LAI, 4 al. 1 LAI, 7 LPGA, 8 LPGA